DEVELOPMENT OF ETHNOSCIENCE-BASED CHEMISTRY TEACHING MATERIALS FOR CLASS IX HIGH SCHOOL STUDENTS - Iqbal, Muhammad; Nurfitriana (Khazanah: Jurnal Mahasiswa, 2021)
Chemistry is one of the sciences that studies the structure or composition of a material, often students have difficulty understanding chemical material. For that to be easy to understand, a teaching material in the form of an ethnoscience-based book is needed. This study aims to determine the validation and practicality of ethnoscience-based book teaching materials. This research is a development research using the 4-D learning model. It consists of four stages of development, namely define, design, develop, and disseminate. The research was carried out until the develop stage, namely the validity test and practicality test. The instrument used is a validity questionnaire that is assessed by the validator, and a practicality questionnaire assessed by teachers and students who are assessed on a Likert scale and analyzed descriptively. Through this research, it is hoped that a valid and practical ethnoscience-based chemistry teaching material can be created to be used as a chemistry learning resource for students. Keywords: Chemistry, Ethnoscience, 4-D model, Validity, Practicality.